Perbedaan Earnings Management pada Pergantian Chief Executive Officer pada Perusahaan Manufaktur yang Terdaftar di BEI - Dewi, Ayu Kristina; Rasmini, Ni Ketut (E-Jurnal Akuntansi; Vol 23 No 2 (2018), 2018)
One of the information contained in the financial statements is information about the company's earnings. Profit information as part of the financial statements is often the target of engineering through opportunistic management actions to maximize its satisfaction. Behavior management to manage earnings as they wish is known as earnings management. Factors affecting earnings management practice is the change of chief executive officer. This study aims to obtain empirical evidence of differences in earnings management at the turn of chief executive officer. This research was conducted at the manufacturing company which registered in Indonesia Stock Exchange Year 2012-2016. The method of determining the sample used is to use purposive sampling. The number of companies that meet the criteria is 34 companies observed. Data analysis technique used is different test Independent Sample t-test. Based on the results of the research, it is known that the CEO of the long period of his tenure proved earnings management that tends to increase profit (income increasing), and also the new CEO of the initial period of his tenure proved to earn earnings management that tends to decrease income (income decreasing). Keywords : Earnings Management, Chief Executive Officer